Pengaruh Brand Equity terhadap Kepuasan Pelanggan di Sekolah Advent Purwodadi, Jawa Timur - Herold Moody Manalu; Francis Hutabarat (Universitas Nusantara PGRI Kediri, 2026)
Education is widely regarded as a critical pathway to children’s future success, prompting parents and communities to invest in high-quality schooling. In a competitive context such as East Java, Indonesia, schools, including boarding institutions, increasingly adopt branding strategies to differentiate themselves and attract students. This study examines the effect of brand equity on customer satisfaction in the educational sector, using Purwodadi Adventist School as the research context. Brand equity was measured through five dimensions: brand awareness, perceived quality, brand association, brand loyalty, and brand assets, while customer satisfaction served as the dependent variable. A quantitative approach was applied, collecting data from 36 students and parents in 2025. Data analysis was conducted using Jamovi software, employing descriptive statistics, correlation analysis, regression analysis, t-tests, and F-tests to evaluate hypotheses. Results indicate that the overall brand equity model significantly predicts customer satisfaction (F = 115, p < .001, R² = 0.950). Among the five dimensions, perceived quality and brand assets had significant positive effects on satisfaction, whereas brand awareness, brand association, and brand loyalty did not show significant impacts. These findings highlight the importance of functional quality and intangible institutional reputation in shaping stakeholder satisfaction.